The Effect of Good Corporate Governance on Financial Performance at PT. Bank Bri, Mandiri and Bni (Persero) Conventional and Sharia Tbk Listed on the Indonesia Stock Exchange 2016 – 2020 - Shakila Keana Nurohmah; Agus Sukoco (Jurnal Ekonomi, 2022)
Study this aim for find influence of GCG (board of directors , board of commissioners and audit committee ) to performance finance (ROA) at PT. Bank BRI, BRI sharia, Mandiri , Mandiri sharia, BNI and BNI sharia Tbk . study this use analysis descriptive With quantitative data , the data source used in this study is a secondary data source. Secondary data is data taken from the financial statements of PT Bank BRI, BRI Syariah, Mandiri , Mandiri Syariah, BNI and BNI Syariah which are listed on the Indonesia Stock Exchange in 2017 6-20 20 published by the Indonesia Stock Exchange through the official website of the Indonesia Stock Exchange ( www.idx.co.id). The data analysis technique in this study uses the classical assumption test, to test the hypothesis using multiple linear analysis tests and T tests. The results showed that partially the Board of Directors (DD) partially had a significant effect on Financial performance (NPM) or HO1 is rejected and H a1 is accepted. Due to the value of sig. DD is smaller than 0.05, i.e. 0.000 <0.05 and the t-count value is greater than t-table, i.e. 4.101>2.06. The Board of Commissioners (DK) partially has no effect on Financial Performance (NPM) or H O2 is accepted and H a2 is rejected. Due to the value of sig. DK is greater than 0.05, which is 0.268 <0.05 and the t-count value is smaller than t-table, namely 1.131 <2.06. The Audit Committee (KA) partially has no significant effect on Financial Performance (NPM) or H O3 is accepted and H a3 is rejected. Because the sig KA value is greater than 0.05, namely 0.07 > 0.05 and the t arithmetic value is smaller than t table, namely 1.888 < 2.06